Exploring strategic priorities for regional agricultural R&D investments in east and central Africa - You, Liangzhi; Johnson, Michael E. (Wiley, 2010)
The 11 countries of East and Central Africa have diverse but overlapping agroclimatic conditions, and could potentially benefit from spillovers of agricultural technology across country borders. This article uses high‐resolution spatial data on actual and potential yields for 15 major products across 12 development domains to estimate the total benefits available from the spread of new agricultural technologies around the region. Market responses and welfare gains are estimated using the Dynamic Research Evaluation for Management model, taking account of current and future projections of local and international demand. Results suggest which crops, countries, and agroclimatic regions offer the largest total benefits. Downloadable data and program files permit different assumptions and additional information to be considered in the ongoing process of strategic priority setting.